Czy Internet ma znaczenie? Opis wydatków polskich partii politycznych na prowadzenie internetowej kampanii wyborczej. - Fabiszewski, Wojciech (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2020)
Media considered the fourth power play a huge role in the election campaign. With the development of the Internet there were new opportunities to promote candidates in the election. The article discussed was the share of spending on online campaigns largest Polish political parties in campaigns in 2011-2015.